From the monotypic to the diverse: three new species of Diguetinus Roewer, 1912 (Opiliones, Eupnoi, Globipedidae) from Mexico - Ochoa-Vázquez, Daniel; Cruz-López, Jesús A.; Rosas-Valdez, Rogelio; Martínez-Salazar, Elizabeth A. (Zootaxa, 2026)
We describe three new species of Diguetinus from the Southern Mexican Plateau and the Sierra Madre Occidental biogeographic provinces. Diguetinus densiseriatus sp. nov. is described based on alpha and beta males and the female. It is distinguished from its congeners by possessing more than two transversal rows of small spines per opisthosomal tergites and at least tergites I–III with more than 40 spines per tergite. Diguetinus tastoanus sp. nov. is described based on a beta male and a female. This species is characterized by a single transversal row of spines per tergite, at least tergites I–III with less than 25 spines per tergite and the anterior propeltidium hump (APH) with a pattern with “III” form. Diguetinus susticacan sp. nov. is described from females only. It differs from remining species by a one row of spines configuration per opisthosomal tergite, at least tergites I–III with less than 30 spines each, APH pattern with “I” form, and by the presence of a light-yellowish band on posterior edge of sternite V. The description of male dimorphism in D. densiseriatus suggests the presence of Alternative Reproductive Tactics (ARTs) within Diguetinus. Additionally, female-predominant sex ratios are discussed, and an identification key is provided for Diguetinus.